Retail and urban regeration in Milan (Ciudades, 2018)
Retail has always been considered an important sector of the Milan economy, but its strategical role in recent urban transformations has been rarely taken in account.Until the half of the 80s, when millions of square metres of brownfields have appeared in the real estate market, only few shopping malls or great supermarkets existed in Milan, whilst most of the great commercial implantations had been located in the outskirts and in the metropolitan area, often along the main radial roads and infrastructural nodes. The possibility of realizing transformation projects introducing new urban functions, among them large commercial sites, in the brownfields, facilitaded by specific national and regional Acts, has rapidly changed the model of retail settlements in Milan. Not all the projects have been successfull, both on the point of view of urban design and of the enhancing of the urban sector in which they were located and on the point of view of the commercial impact.
Keywords: Milan; urban transformations; urban retail